Water induced sediment levitation enhances downslope transport on Mars - Jan Raack (Nature Portfolio, 2017)
Downslope sediment transport on Mars is reported, but the transport capacity of unstable water under low pressures is not well understood. Here, the authors present a newly discovered, highly reactive transportation mechanism that is only possible under low pressure environments.